Sufism Literature: Divinity Philosophy in Taufiq al-Hakim’s Short Story Arinillah - Zulhelmi Zulhelmi; Nurchalish Nurchalish; Syarifuddin Syarifuddin; Muhammad Walidin; Rahlina Muskar (Buletin Al-Turas, 2023)
PurposeThis article aimed to know how a Modern Egyptian writer, Taufiq al-Hakim, enlightened his readers to believe Allah's existence and could feel His presence more closely. MethodAs qualitative research, this article relied on verbal data in the form of sentences or paragraphs available in the short story. In collecting the data, the authors read carefully Arinillah, Taufiq al-Hakim’s short story; and made some notes on sentences or paragraphs considered to indicate ways of enlightening Allah’s existence. The data were analyzed qualitatively using Sufism literature theories to identify Taufiq al-Hakim’s ideas of Allah’s existences and his ways of educating the readers to believe in Allah. Results/FindingsTaufiq al-Hakim's ways of educating his readers to believe in Allah’s existence through the storyline beginning with curiosity and ending with regret. He did not curb the readers’ curiosity to know Allah's existence, but left them to play in the adventure of Sufistic spiritual imagination. At the end of the story, they regretted because they with their mind were not able to identify the existence of Allah, the greatest. ConclusionThe article concluded that Arinillah storyline was Taufiq al-Hakim’s way in interpreting hadith of the Prophet Muhammad SAW regarding prohibition to think Allah’s substance; and it was not true that he violated such a prohibition.